Just-in-time systems and Euro-Japanese industrial collaboration - Holl, Uwe; Trevor, Malcolm, 1932- (Routledge, 2019)
Just In Time (JIT) systems in the context of the relations between Japanese manufacturers in Europe and European suppliers of parts and materials have so far received little attention. Yet Japanese involvement in local production is having an impact on European companies in this area. Whether in cooperation or competition with Japanese companies,